How Do Police Prevent Corruption? The Role of Community Police Officer (Bhabinkamtibmas) in Preventing Misuse of Village Funds in Cipeundeuy Police Department - Azkiya Pamungkas Rosadi (Advances in Police Science Research Journal, 2021)
Increasing the village budget from year to year, solely aimed at equitable development that can be felt up to the village community. From year to year village funds have increased significantly in line with the increase in corruption cases committed by various parties concerned, especially the Village Head. President Joko Widodo instructed to tighten supervision of village fund management. Bhabinkamtibmas was given the task of spearheading the supervision of village funds as stated in the memorandum of understanding made by the Ministry of Villages, the Ministry of Internal Affairs and the Indonesian National Police. The formulation of the problem in this research is how the role of Bhabinkamtibmas Cipeundeuy Sector Police in preventing misuse of village funds and factors that hinder that role. This research is intended to describe and analyze the problems raised by the author, so that it can be useful for the development of knowledge and for the leadership policy. The study was conducted with a qualitative approach, using descriptive analysis writing methods, as well as data collection techniques with active observation, semi-structured interviews, and study of related documents. Data validity is supported through source triangulation techniques, and methods. Stages of data analysis through data reduction, data presentation, to the conclusion. The results found that Bhabinkamtibmas Cipeundeuy Sector Police had not been able to carry out all the tasks assigned. Sehinnga, there is no match between theory and concept with the facts and data in the field. The role is not yet maximally very closely related to several factors that hinder it, namely the condition of Bhabinkamitbmas itself to the conditions of the target communities. The conclusion of this research is that Bhabinkamtibmas has not been maximized in carrying out its role to prevent misuse of village funds. Therefore, the writer suggests that a policy on preventing village funds from the National Police be implemented and for the Polres and Polsek ranks to be able to apply analysis and evaluation appropriately and according to procedures. The author also recommends Bhabinkamtibmas to use the android application to facilitate monitoring of village funds.